The bird flu in mind of Hungarian consumers- lesson and experiences of a direct-question survey - Kasza, Gyula; Lakner, Zoltán (Acta Agraria Kaposváriensis, 2006)
The emergence of avian flu in Europe means new challenges for the Hungarian food chain, highlighting the importance of risk-communication to the consumers. Based on a direct-question survey in end of 2005, the article analyses the consumers’ preference structure and risk-perception. Basic information source is the electronic and printed media, but – especially in case of lower qualified consumers âˆ’ the effect of friends and relatives is considerable, too. The level of thrust is especially high in researchers and medical authorities. This fact should be more utilised in communication. The pro-active strategy of Hungarian Poultry Product Council can be evaluated as a positive one. Beside the negative effects (decreasing consumption), the avian flu problem enhances the importance of place of origin of products. The system of factors, influencing consumer behaviour was analysed by the Fishbein-Ajzen model. Utilising the structural equation approach, it was possible to determine the system factors, influencing the consumer behaviour. It became obvious, that the attitudes of consumer exercise a determining effect on the practical behaviour in poultry consumption.
Keywords: consumer research; attitudes; Fishbein-Ajzen model